Edukasi Mitigasi Bencana dan Konservasi Lingkungan Berbasis Pendekatan Spasial dan Kearifan Lokal bagi Siswa Sekolah Dasar di Pesisir Teluk Tomini - Pambudi, Moch Rio; Masruroh, Masruroh; Ninasafitri, Ninasafitri; Aris, Ayub Pratama; Melo, Ramla Hartini; Pratama, M. Iqbal Liayong; Asrul, Asrul (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to introduce a spatial approach in disaster mitigation education and environmental conservation based on local wisdom to elementary school students in the coastal area of Tomini Bay. The activity was carried out at SDN 3 Kabila Bone and involved 25 students from grades 1 to 6, selected based on school recommendations and willingness to participate. The method used was classic lectures with the aid of visual media, such as maps of the Tomini Bay area and presentations accompanied by strengthened narratives of local wisdom. The activities took place in an enjoyable learning atmosphere, accompanied by question-and-answer sessions and interactive discussions. The success of the activity was evaluated through direct observation of three cognitive aspects of the students: their ability to recall, understand, and apply the material. The results showed that most students were able to achieve a high level of understanding in all aspects, particularly in applying the knowledge to real-life contexts. The spatial approach made it easier for students to recognize their home region and visually understand potential risks, while local values strengthened students’ connection to their social and cultural environment. This approach is simple, adaptive, and can be implemented in elementary schools in coastal areas with limited access to technology. These findings support the effectiveness of the spatial-cultural approach as a relevant, grounded, and widely replicable model for disaster mitigation education and environmental conservation in other regions with similar characteristics.